Beyond Paradigmatic Tensions: Toward Context-Sensitive Educational Research in Indonesia - Aditya, Dionisius R (Studia Philosophica et Theologica, 2026)
Indonesia's multicultural education system presents a unique challenge for educational research. This paper examines the persistent paradigmatic tension between positivism and interpretivism in Indonesian educational research and argues for a context sensitive mixed methods approach that rise above this traditional dichotomy. While positivism offers valuable tools for identifying broad patterns and informing national policy through quantitative methods, it frequently fails to capture the cultural, linguistic, and socioeconomic complexities at the local level. Conversely, interpretivism provides deep and contextual understanding through qualitative inquiry but often struggles to achieve broader applicability and policy relevance. Through a critical comparative analysis of paradigm foundations and examination of Indonesian case studies this paper demonstrates how a reflexive, ethically grounded mixed-methods praxis can bridge this divide. The paper contributes a framework for Indonesian educational researchers that emphasizes paradigmatic reflexivity, methodological flexibility, ethical consideration of power relations, and active community engagement.